KESANTUNAN TINDAK TUTUR DIREKTIF DALAM TALK SHOW SATU JAM LEBIH DEKAT DI TV ONE (TINJAUAN PRAGMATIK) - Syah, Nur Aini (Sunan Kalijaga State Islamic University Yogyakarta, 2017)
The aim of this research are to explain the politeness of directive speech acts and politeness strategy, which supports the effectiveness of the talk show. This research is a descriptive qualitative research. The data resources are spoken data from three episodes of Satu Jam Lebih Dekat Talk Show on TV One. The technique of data sampling is determined by purposive sampling. The data validation technic in this research is triangulation technic. The result of the research shows that the types of directive speech acts in Satu Jam Lebih Dekat are to please, to request, to ask, to order, to invite, and to forbid. The politeness strategies of Satu Jam Lebih Dekat are bald on record, positive politeness, negative politeness, and off record. The politeness of directive speech acts supports the effectiveness of the talk show because of some factors, such as types of directive speech act and politeness strategy.